Family-centered palliative care in pediatric oncology - López-Ibor Aliño, Blanca (2022)
Cancer is a disease that affects one child for every 200 adults. It is the second leading cause of death in children aged 0-14 years after accidents. 80% of children diagnosed with cancer are cured of their disease in our country. However, approximately 20% eventually die from the disease or the side effects of treatment. Once the severity of the disease is known and therefore its consequences, it is essential to try to integrate the disease into the normal life of the child, the family, and the surrounding environment. The aim is to turn the child into a physically, psychologically, socially, and spiritually healthy adult. To achieve this, the child must be the center of our work and should be attended to by a multidisciplinary team. Palliative Care should be started from the time of diagnosis for children with poor or no possibility of cure.  For the rest of the children, it should be started in case of relapse. In the last days of life of any child, it is always offered the possibility of receiving this care at home, in the hospital, or in a combined modality (Mixed Palliative Care), where they receive part of the care at home and at the end of their life they move to the hospital to live their last days there.  Medicine should not only focus on the patient, but also the family.